Reducing pest incidence for quality coconut - Mohan, Chandrika; Rajkumar, A Joseph (Indian Horticulture, 2018)
A planned and holistic programme through awareness creation, capacity building on incursion management and strict quarantine are essentially warranted to combat invasions due to such biosecurity threats. Creation of an incursion management team comprising of experts from all disciplines as well as an emergency preparedness module would be the need of the hour to tackle accidental introduction of invasive pests into the country. With the impact of climate change and modulation in pest dynamics, a salubrious approach is very critical for effective implementation of IPM strategy. Farmer-participatory community mode would be given the top most priority for successful translation of technologies and field reality.